Air–soil heat exchangers for heating and cooling of buildings: Design guidelines, potentials and constraints, system integration and global energy balance - Hollmuller, Pierre; Lachal, Bernard (Applied energy, 2014)
•Overview of analytical models, numerical simulation, system integration and overall energy balance.•Climate independent design guidelines for amplitude dampening of yearly or daily temperature oscillation.•Highlighting of potentials and limits for preheating and cooling of buildings.•Comparison with other passive cooling techniques.•System integration (conflicts and synergies with other components) and derivation of overall energy balance. Air–soil heat exchangers for heating and cooling of buildings are analyzed under various aspects. Based on the analytically resolved case of a constant airflow subject to sinusoidal temperature input, we start by deriving climate independent design guidelines, for dampening of the daily and/or the yearly temperature oscillation. In a second step, constraints and potential of buried pipe systems are analyzed for the case of a typical Central European climate, for which the constraint between climate and comfort threshold induces a fundamental asymmetry between preheating and cooling potential. Finally, it is shown that the net yield of an air–soil heat exchanger has to take into account more than the mere input–output temperature differential.